(893) Numerical Control Series. Programming for NC سلسلة التحكم العددى . البرمجة من اجل التحكم العددىNC - AlWalid El Shafei. (معهد التخطيط القومى, 2024)
WHAT IS MEANT BY PROGRAMMING?Programming is the process of writing the group of instruc- tions telling the numerically controlled m/c where to move the cutter in order to form a part. This involves the following:1) Defining the part to be cut2) Describing the sequence of m/c's operations needed to obtain the final shape3) Defining the location of the tool relative to the w/p during each of the m/c'g operations4) Describing the sequence of events which occur as the location of the tool changes.